2014
DOI: 10.1007/s12630-014-0286-7
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative considerations of the patient with malaria

Abstract: Purpose Malaria is a life-threatening infectious disease caused by the Plasmodium parasite. Increased global travel has resulted in an escalation in the number of imported cases seen in developed countries. Patients with malaria may present for surgery in both endemic and nonendemic countries. This article reviews the perioperative considerations when managing patients with malaria. Source A literature review of anesthesia, perioperative care, and malaria-related articles was performed using the MEDLINE Ò , EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…However, the pathophysiological changes caused by malaria infections, including excessive releases of cytokines and chemokines such as tumor necrosis factors and interleukin-2, could alter the healing process postoperatively [30]. Previous studies have suggested that surgery may weaken patients' immune systems, increasing their susceptibility to malaria and its complications or to other pathogens [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pathophysiological changes caused by malaria infections, including excessive releases of cytokines and chemokines such as tumor necrosis factors and interleukin-2, could alter the healing process postoperatively [30]. Previous studies have suggested that surgery may weaken patients' immune systems, increasing their susceptibility to malaria and its complications or to other pathogens [16].…”
Section: Discussionmentioning
confidence: 99%
“…Children present with different surgical pathologies, respond differently to anesthesia, and have special perioperative needs associated with high perioperative mortality [5,7]. The vast majority of research on perioperative morbidity and mortality is from developed countries [7][8][9][10][11][12], and the number of studies that have looked at the in uence of medical comorbidities unique to sub-Saharan Africa are limited [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the multi-system manifestations seen are because of the changes in the parasitized erythrocyte; these show a reduced membrane deformability and increased fragility, with accelerated haemolysis leading to an anaemia that may be complicated by direct bone marrow suppression. 4 Increased adherence to the vascular endothelium causes sequestration of red blood cells and microvascular capillary obstruction of the cardiac, renal, hepatic, splenic, and cerebral circulations. Pro-inflammatory cytokines, such as interleukin-1 and tumour necrosis factor, may generate a systemic inflammatory response.…”
Section: Malariamentioning
confidence: 99%
“…It has been suggested that surgical stress may cause reactivation of dormant Plamodium vivax or Plamodium ovale. 4 Preoperative evaluation of patients with malaria should include an assessment of the severity of infection and degree of organ impairment (Table 1).…”
Section: Malariamentioning
confidence: 99%
“…Furthermore, the difficulty of creating efficient vaccines and also adverse side effects of the existing antimalarial drugs highlight the urgent need for new antimalarial drugs for treatment of malaria. In addition, malaria-associated hypoglycemia has been reported during malaria parasite infection, and is one of all most causes of death [7][8][9].…”
Section: Introductionmentioning
confidence: 99%